Patients’ Knowledge About the Endoscopic UltrasoundGuided Fine Needle Aspiration of Pancreas Is Not Enough - Shen, Linxia; Lu, Jianying; Gu, Ying; Shen, Wenjuan; Qi, Junfang (Turkish Journal of Gastroenterology, 2023)
Background: The aim of the study is to evaluate the extent to which patients acquired necessary knowledge about pancreatic endoscopic ultrasound-guided fine needle aspiration and assess what should be more focused on in the informed consent process. Methods: Adult patients enrolled in this study had pancreatic lesions confirmed by regular imaging and planned to undergo the first pancreatic endoscopic ultrasound-guided fine needle aspiration. These patients were asked to complete a questionnaire, including indications, possible results, downstream events, the risk for false-negative and malignant lesions, and so on. Then we conducted a longterm follow-up of these patients to obtain the final results. Results: Most people (94.25%) correctly recognized that the indication of pancreatic endoscopic ultrasound-guided fine needle aspiration was to exclude malignant lesions. Almost all patients knew that the results could be benign or malignant, while the number of people who were aware of non-diagnostic (22%), indeterminate (18%) outcomes, and the possibility of further testing (20%) after the endoscopic ultrasound-guided fine needle aspiration has decreased significantly. Finally, we got that the false-negative rate and percentages of malignancy were 17.81% and 83.91%, while 98% of participants did not recognize that there is a false-negative risk of endoscopic ultrasound-guided fine needle aspiration and more than 2/3 of participants did not know how much risk they might have for malignant lesions. Conclusions: A high proportion of patients who received endoscopic ultrasound-guided fine needle aspiration could identify the indication for this procedure but remained unaware of possible outcomes, downstream events, especially the risk for false-negative and malignant lesions. It is necessary to improve the quality of dialogue between clinicians and patients, and the information about the risk of false-negative and malignancy may need to be emphasized in the informed consent process. Cite this article as: Shen L, Lu J, Gu Y, Shen W, Qi J. Patients’ knowledge about the endoscopic ultrasound-guided fine needle aspiration of pancreas is not enough. Turk J Gastroenterol. 2023;34(6):611-617.